Effect of Financial Staff Competence and Arkas Use on BOS Reporting Timeliness with Leadership as Moderator - Endang (Yayasan Amerta Insan Unggul, 2025)
This study aims to investigate the influence of financial staff competency and the utilization of the ARKAS application on the timeliness of reporting School Operational Assistance (BOS) funds, as well as to examine the moderating role of leadership within vocational schools under the Gunung Putri Regional Coordination, Bogor Regency. Timely reporting of BOS funds is a critical component of school financial accountability and is strongly affected by internal organizational factors, including human resource capabilities and the effectiveness of information technology use. Employing a quantitative research design with a survey approach, data were collected through structured questionnaires administered to financial staff working in the selected schools. The data were analyzed using moderated regression analysis (MRA) supported by SPSS software to assess both direct and moderating effects. The findings reveal that financial staff competency and the utilization of the ARKAS application each exert a positive and significant effect on the timeliness of BOS fund reporting. Furthermore, leadership is found to strengthen the relationship between both independent variables and the dependent variable, indicating its critical role in enhancing reporting performance. This study contributes to the understanding of effective BOS fund management at the school level by highlighting the importance of developing human resource competencies, optimizing technology-based financial applications, and reinforcing leadership practices. The implications of this study emphasize the need for schools to invest in capacity building and digital system integration to improve reporting accuracy, transparency, and accountability.